EUGENIA, CORPO E EDUCAÇÃO SEXUAL: IMAGENS E INTERPRETAÇÕES SOBRE MULHERES NA OBRA DE RENATO KEHL (1920-1930) - Francescon , Marcela Cristiane Cavalheiro Miranda (2017)
Abstract: It was analyzed in this thesis the construction of the place of woman and the female body in the speech of the physician and eugenist Renato Kehl in the years 1920 and 1930, trying to understand the speech and strategies of the author to intervene in the process of social reform, such as sexual education, matrimonial control and human reproduction. The woman appears in the work of Renato Kehl occupying central attention, as arbiter of the marriage to choose an intercourse able to elevate the racial quality of the Brazilian type in eugenic reproduction. The normalization of female behavior was defended by this eugenist, so that questions about sexuality, corporal measures, ideal of racial beauty and social hygiene were aspects that permeated the discussions about the will to regenerate the Brazilian population, based on differences and rigid racial, sexual and biological hierarchies. As has been emphasized by historiography, the eugenic speech produced by a group of intellectuals engaged in projects to modernize the country and define the nation developed policies of social intervention based on the determinist and racialist theories that began in the late nineteenth century and extended largely from the early decades of the twentieth century. It was attempted to perceive how the representation projected by eugenics on the construction of a normal woman, whether in the Hellenic perfection of the body or in the good education for matrimony and motherhood, reflected the ideal of family that would represent the modern Brazilian nation.